Overweight in an urban Siberian population: 12-year trends - E. V. Akimova; E. I. Gakova; R. Kh. Kayumov; E. Yu. Zagorodnykh; O. V. Smaznova; M. M. Kayumova; V. V. Gafarov; V. A. Kuznetsov (Кардиоваскулярная терапия и профилактика)
Aim. To assess the levels of body mass index (BMI) in an urban Siberian population of 25-64-year-old men; to investigate the prevalence of overweight (OW) and its dynamics over the 12-year period of the population monitoring. Material and methods. The study included two randomised, electoral list-based samples of 25-64-year-old male residents of one Tumen City district. Each sample included 1000 individuals (250 in each 10-year age group – 25-34, 35-44, 45-54, and 55-64 years). The response rates for the first and second cardiologic screenings (1996 and 2008) were 79,5% and 85,2%, respectively. Results. In the male Tumen population, OW was more prevalent in middle-aged people. Obesity (O) was more prevalent in men with primary education or non-strenuous manual occupation. No considerable social gradient in OW was observed. Conclusion. Over 12 years, the male Tumen population, aged 25-64 years, has demonstrated an increase in O and OW prevalence, mostly due to increasing BMI levels in younger age groups. The 12-year trends have shown that the increase in O prevalence takes place one decade earlier.